Study on the hydraulic conductivity by constant and falling head methods for pervious concrete - BATEZINI,R. (2015)
The main goal of this paper is to show the analysis of the permeability characteristics of three different mixes of pervious concrete produced with the variation of the coarse aggregate size. Two different test methods were used to achieve the hydraulic conductivity of the samples: falling head and constant head permeability tests. Based on test results it is concluded that the pervious concrete mixes have shown to be good drainable materials. Besides, it was found that the permeability of the mixtures does not seem to depend on the size and gradation of the coarse aggregate.